GamifiCHI: thematized badges for HCI courses - Pereira, Roberto; Rodrigues, Kamila R. H.; Silveira, Milene Selbach (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Schools and universities face the great challenge of keeping students engaged in learning activities, and research communities strive to keep and share their history and culture. Among several methodological approaches, gamification has been used as a resource combined with teaching methodologies to engage and keep students participating. However, gamification strategies have been mainly applied detached from the substantial meaning from the disciplines and activities worked with students. In this paper, we propose to thematize gamification elements, such as badges, with relevant content for HCI classes. We propose a set of 50 badges thematized with distinguished researchers from the HCI community, both in local and global scenarios, and suggest a structure to support using and adapting this set of badges to gamify HCI classes. Exemplifying badges applicability and contribution, we present results from their instantiation to gamify three HCI courses in three different universities. The set of thematized badges is openly available for download and reuse.